Effect of novel biomodification strategies on bonding to pulp chamber dentin - An In Vitro study - Saranya Radhakrishnan; Darshana Devadiga (Wolters Kluwer Medknow Publications, 2023)
Context: Adhesion to dentin remains a tough challenge due to its heterogeneous composition, complex histologic structure and high tubular content, warranting the need to investigate methods to improve the bond strength of the commonly used access restorative materials to pulp chamber dentin. Aims: To evaluate the effect of dentin biomodification using 6.5% grape seed extract and a 980 nm diode LASER on the shear bond strength of resin-based bonded restoration to pulp chamber dentin. Methods and Materials: Access cavities were prepared in 42 extracted human maxillary premolars, which were then sectioned in a buccolingual direction. The samples were serially immersed in 5.25% NaOCl for 40 minutes and 17% EDTA for 3 minutes and allocated into three groups: the control group, the group pre-treated with 6.5% grape seed extract (GSE) and the group pre-treated with a 980 nm diode light amplification by stimulated emission of radiation (LASER). All the samples were restored with resin composites and subjected to shear bond strength testing using a universal testing machine. Statistical Analysis Used: Statistical analysis was done using SPSS version 23 software. Results: The mean shear bond strength was highest in the group pre-treated with GSE, followed by that pre-treated with diode LASER and finally in the control group. Conclusions: Dentin biomodification using both chemical and physical agents such as grape seed extract and diode LASER was shown to improve the shear bond strength of resin composite endodontic access restorations to the pulp chamber dentin.